Pulp Revascularization in Three Immature Permanent Mandibular Molars with Necrotic Pulps: A Case Series - Hajizadeh, Samane; Youzbashi Zadeh, Reza; Vatanparast, Negin (Iranian Endodontic Journal, 2019)
The management of necrotic immature permanent teeth, with blunderbuss root anatomy, is a treatment challenge. Treatment protocols include root canal apexification, creation of an apical plug and recently, regeneration and revascularization protocol (RRP). The latter may have the advantage of continued root development. The main purpose of this case series was to describe the RRP of three necrotic immature permanent mandibular molars with open apices. RRP involved accessing the pulp chamber, disinfecting the root canal system with copious irrigation using 2.5% sodium hypochlorite, applying triple antibiotic paste/calcium hydroxide as an intracanal medicament and sealing the access cavity. After three weeks, the medicament was removed and the apex was irritated with a K-file to induce blood-clot formation inside the pulp canal space; which would provide a suitable matrix for new tissue in-growth. Mineral trioxide aggregate was employed to seal the canal orifices before final restoration. During follow-up sessions, patients were asymptomatic and root development seemed to be in progress. Therefore, it seems that with proper case selection, regeneration and revascularization can be considered as a suitable alternative for the apexification of necrotic immature teeth. Keywords: Dental Pulp Necrosis; Mineral Trioxide Aggregate; Revascularization